2004
DOI: 10.1017/s1138741600004819
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in Discriminating Blood Glucose Levels in a Sample of Children with Type 1 Diabetes

Abstract: The present study explores accuracy in estimating blood glucose levels (BGL) in children with type 1 diabetes and analyzes the kinds of symptoms and cues which they use to estimate their BGL. Forty two children with type 1 diabetes completed a SI/IC-3 scale consisting of 28 items (22 symptoms and 6 feelings), indicating those which they perceived at the time and their intensity. They estimated their BGL and gave reasons for their estimation, before having a blood glucose level analysis performed. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Therefore, studies have been reported with the effective use of a variety of biological data to help to improve the control of blood glucose level. A variety of methods have been proposed on the subjective blood glucose estimation made by patient [11], on the capillary blood glucose estimation using interstitial fluid [4,10] and on the insulin pump control using blood glucose levels [9]. However, there are not so many reports concerning the predictions of the future blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies have been reported with the effective use of a variety of biological data to help to improve the control of blood glucose level. A variety of methods have been proposed on the subjective blood glucose estimation made by patient [11], on the capillary blood glucose estimation using interstitial fluid [4,10] and on the insulin pump control using blood glucose levels [9]. However, there are not so many reports concerning the predictions of the future blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%